The Growth-Suppressive Function of the Polycomb Group Protein Polyhomeotic Is Mediated by Polymerization of Its Sterile Alpha Motif (SAM) Domain. - Robinson, A.K.; Leal, B.Z.; Chadwell, L.V.; Wang, R.; Ilangovan, U.; Kaur, Y.; Junco, S.E.; Schirf, V.; Osmulski, P.A.; Gaczynska, M.; Hinck, A.P.; Demeler, B.; et al. (Journal of Biological Chemistry, 2012)
Polyhomeotic (Ph), a member of the Polycomb Group (PcG), is a gene silencer critical for proper development. We present a previously unrecognized way of controlling Ph function through modulation of its sterile alpha motif (SAM) polymerization leading to the identification of a novel target for tuning the activities of proteins. SAM domain containing proteins have been shown to require SAM polymerization for proper function. However, the role of the Ph SAM polymer in PcG-mediated gene silencing was uncertain. Here, we first show that Ph SAM polymerization is indeed required for its gene silencing function. Interestingly, the unstructured linker sequence N-terminal to Ph SAM can shorten the length of polymers compared with when Ph SAM is individually isolated. Substituting the native linker with a random, unstructured sequence (RLink) can still limit polymerization, but not as well as the native linker. Consequently, the increased polymeric Ph RLink exhibits better gene silencing ability. In the Drosophila wing disc, Ph RLink expression suppresses growth compared with no effect for wild-type Ph, and opposite to the overgrowth phenotype observed for polymer-deficient Ph mutants. These data provide the first demonstration that the inherent activity of a protein containing a polymeric SAM can be enhanced by increasing SAM polymerization. Because the SAM linker had not been previously considered important for the function of SAM-containing proteins, our finding opens numerous opportunities to manipulate linker sequences of hundreds of polymeric SAM proteins to regulate a diverse array of intracellular functions.